Development and analysis of a polygenerational smart energy hub for sustainable communities. (15th December 2020) - Chehade, Ghassan; Dincer, Ibrahim
Highlights: An economic case study is performed to balance Ontario's energy requirements. The system performance is evaluated through thermodynamic analysis. The present plant is designed to have carbon capture capabilities with no emissions. Abstract: A new community based polygeneration smart energy system is proposed to meet the demands of a community in a sustainable manner and applied to case study where we aim to balance Ontario's energy requirements while minimizing carbon emissions. In this case study, the smart energy hub utilizes a 30 MW small modular nuclear reactor which provides a unique and novel gas system at high temperature level integrated for the production and transportation of chemical energy; this occurs through a circuit in which an endothermic reaction (steam methane reforming plant) is connected to an exothermic reaction (methanation plant) and appears to be an attractive and preferable solution that meets the environmental requirements for a stable and efficient energy supply process. Complex multiscale subsystems are developed, modeled and simulated in the Aspen plus. Thermodynamic analyses on different sub-plants are presented, considering natural gas as the main feedstock, and incorporating power and heat production through chemical looping. The energy hub is capable of generating 10.8 MW of electricity and supplying 17.9 MW of heat for district heating. Hence, the overall energy and exergy efficiencies of the smart energy system are found to be 54% and 76% respectively. Also, a power to gas plant is integrated into the energy hub for the production of anhydrous ammonia with a capacity of 1816.22 tons/day and 100% carbon capture capabilities. Moreover, the impact of varying the input proportions of the system on the products and functionality of the energy hub are investigated.